Comparing monomodality treatments of low--‐ grade intracranial arteriovenous malformation at hospital Kuala Lumpur between 2008 and 2011: a retrospective study - Rosli, Fadzlishah Johanabas (2015)

(untitled)
Title Comparing Monomodality Treatments of Low-Grade Intracranial AVM at Hospital Kuala Lumpur between 2008 and 2011: A Retrospective Study Authors Fadzlishah Johanabas Rosli1,2, Mohammed Saffari Mohammed Haspani1, Abdul Rahman Izaini Ghani2 1Department of Neurosurgery, Hospital Kuala Lumpur, Kuala Lumpur, Malaysia 2Department of Neurosciences, Universiti Sains Malaysia, Kubang Kerian, Malaysia Introduction Arteriovenous malformation (AVM) is an abnormal connection between arteries and veins, which bypasses the capillary system. Although it can appear in any location, this vascular anomaly is widely known due to its occurrence in the central nervous system. AVMs are one-tenth as common as saccular aneurysms. The rate of haemorrhage in untreated patients is between 2 to 4 percent per year, with a mortality rate of 5 to 10 percent. There are several treatment modalities for AVMs: microsurgery, endovascular embolization and stereotactic radiosurgery (SRS). Surgical excision remains the gold standard treatment for accessible, low-grade AVM. However, resection of deep-seated AVMs, such as within the thalamus and the brainstem, remains a therapeutic challenge. Objectives To establish an understanding whether SRS or embolization can achieve satisfactory obliteration of AVM nidi for patients as opposed to microsurgical excision, and to look for incidence of complications such as haemorrhage and permanent neurological deficit following treatment, for up to 3 years. Methods This is a retrospective review of records study. The data is acquired from case notes of patients with intracranial AVM of Spetzler-Martin grades I to III who underwent monomodality treatment at Hospital Kuala Lumpur between 2008 and 2011. The patients were followed-up with imaging for up to 3 years from the date of treatment. A total of 81 patients were recruited in this study, where 30 underwent microsurgical treatment, 27 underwent embolization, and 24 underwent SRS. Results Total obliteration of AVM nidus was achieved in 96.7% of patients who underwent microsurgery, 8.7% of patients who underwent embolization and 79.2% of patients who underwent SRS. 4 patients who underwent microsurgery passed away (3 directly related to surgery), and 4 patients who underwent embolization passed away (3 directly related to procedure), whereas no mortality was seen in the SRS group. The modified Rankin Scale (mRS) for all three groups showed an improving trend, with the microsurgery group showing the best improvement (from 70% at 3 months to 92.3% at 3 years showing favourable mRS scores). Conclusion The AVM nidus obliteration for each treatment group is comparable to the meta-analysis published in 2011, where successful AVM obliteration was achieved in 96% (range 0% - 100%) after microsurgery, 38% (range 0% - 75%) after SRS and 13% (range 0% - 94%) after embolization. Each modality had its own set of complications; however, most of the patients in all three groups had either static or improved modified Rankin Scale (mRS) at the end of the 3-year follow-up. As we can achieve good AVM nidus obliteration using microsurgery and SRS, it will be good to explore and develop these treatment options further. Embolization, however, still plays a vital role in complicated cases (eloquent regions, large AVM).